Nutritional quality of amaranth (Amaranthus) silage in response to forage airing and addition of lactic bacteria - Zubillaga, María Fany (2024)
Fil: Zubillaga, María Fany. Universidad Nacional de Río Negro. Río Negro; Argentina.